Characterisation of the dielectric properties of rhinoceros tissue using computer simulation and physical tissue phantom models - Van Zyl, Floris Johannes (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.